2018
DOI: 10.23822/eurannaci.1764-1489.51
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab in chronic spontaneous and inducible urticaria: a 9 year retrospective study in Portugal

Abstract: Describe the safety and long-term use of omalizumab in chronic urticaria (CU), both spontaneous (CSU) and inducible (CIndU). Retrospective chart-review (2006-15) of CU patients treated with omalizumab for ≥ 6 months. Statistical analyses: descriptive statistics, Mann-Whitney, generalized linear models. 23 patients with CSU (3 men), 3 with CIndU (2 men). Generalized linear models showed UAS reduction per omalizumab administration of 16% in CIndU and CSU and UAS7, of 15% in CIndU, and 20% in CSU. DLQI score at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
(44 reference statements)
1
6
0
Order By: Relevance
“…For the patients in our study cohort who achieved remission free of omalizumab, average treatment duration was 21 months. Another important finding in our cohort, also shown by Metz et al 19 and Marcelino et al20 is that there is no decrease in the effect of omalizumab when reinitiating after it has been discontinued.…”
supporting
confidence: 85%
See 3 more Smart Citations
“…For the patients in our study cohort who achieved remission free of omalizumab, average treatment duration was 21 months. Another important finding in our cohort, also shown by Metz et al 19 and Marcelino et al20 is that there is no decrease in the effect of omalizumab when reinitiating after it has been discontinued.…”
supporting
confidence: 85%
“…Overall, approximately 41% to 48% of patients in clinical trials 2,5,7 and 12% to 23% in “real‐world clinical setting” 13,19,23‐26 do not have a complete or significant response to omalizumab therapy. However, there are also some studies of omalizumab in the literature without any non‐responder patients 20 . Relatively high percentage of non‐responders in our cohort may be due to high number of patients and, being more resistant to various therapy options which are usually referred to our tertiary research center.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Furthermore, most of the previous studies are limited by the small number of patients and lack of detailed analysis of subscales. A total 89 of patients with CSU were enrolled in seven studies (n = 2-28) and a significant improvement in DLQI scores was obtained following omalizumab treatment (Kai, Flohr, & Grattan, 2014;Kaplan, Joseph, Maykut, Geba, & Zeldin, 2008;Lefévre, Deleuran, & Vestergaard, 2013;Marcelino et al, 2018;Savic et al, 2015;Subramaniyan & Chopra, 2016;Vestergaard & Deleuran, 2010). Accordingly with our results, the decrease in DLQI scores was most significant during the first month of treatment and then stabilized as long as the treatment is continued (Kai et al, 2014;Lefévre et al, 2013;Vestergaard & Deleuran, 2010 Consistently with our findings, two previous studies including 14 and 18 patients have reported a significant decrease in CU-Q2oL-total scores which was maintained up to 6 months (Büyüköztürk et al, 2012;Larrea-Baca & Gurpegui-Resano, 2017).…”
Section: Discussionmentioning
confidence: 99%